Implementation of a Distributed Control Experimentation Platform - Muñoz, Mario A. (2007)
In this work, we present the implementation of a planar temperature grid plant. This plant emulates the working of a control system that is designed to maintain a constant temperature over a surface. The behavior of the implemented plant presents characteristics difficult to describe in mathematical terms like disturbances, interferences, deviations, and temperature gradients. We describe the functional characteristics of the system and its application in the study of distributed control systems in an educational environment. To test the working of the plant we present the obtained results with two resource allocation strategies such as control algorithms.